Export Management and Market Strategy of Indonesian Fish Meal for Aquaculture Farm Feeds to Saudi Arabia - Pramono, Anton; Riani, Etty (Pascasarjana, Mataram University, 2024)
This study examines the potential of export management and marketing strategies of Indonesian fishmeal for aquaculture animal feed in Saudi Arabia. Fishmeal, a high-protein feed, is essential in aquaculture. From this background, the researcher found the problem object that although Saudi Arabia is expanding its aquaculture sector, the country has not imported fishmeal with HS code 2301 from any country. Considering the established fishmeal industry, this study aims to investigate Indonesia's potential as a supplier. This study applies qualitative descriptive methods to analyze export management, and market strategy and identify challenges in entering the Saudi market. Based on this study, the author found benefits from the findings. The findings emphasize the need for strategic partnerships, regulatory understanding, and market penetration tactics to enable the success of Indonesian fishmeal exports to Saudi Arabia